1992
DOI: 10.1302/0301-620x.74b1.1732260
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of the proximal femur. A three-dimensional radiographic analysis

Abstract: Biological fixation of cementless femoral implants requires primary stability by optimal fit in the proximal femur. The anatomy of the bone must then be known precisely. We analysed in vitro the accuracy of bone measurements of 32 femurs and compared the dimensions obtained from radiographs and CT scans with the true anatomical dimensions. Standard radiographs gave only a rough approximation of femoral geometry (mean difference: 2.4 +/- 1.4 mm) insufficiently accurate to allow selection of the best fitting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
172
6
6

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(206 citation statements)
references
References 0 publications
19
172
6
6
Order By: Relevance
“…Charnley [13] considered it to be a factor under the control of the surgeon at the time of hip replacement surgery, the more lateral position of the femur with greater horizontal offset was said to increase the range of motion and decrease the incidence of impingement of the femoral head on the pelvis thus decrease the post-operative complications. Though CT scan is more accurate, the plain radiography is definitely the most cost effective and convenient method for offset measurement in the developing countries like India [14]. Our data showed that the average horizontal offset was 3.85 cm and 3.57 cm in male and female respectively.…”
Section: Methodsmentioning
confidence: 67%
“…Charnley [13] considered it to be a factor under the control of the surgeon at the time of hip replacement surgery, the more lateral position of the femur with greater horizontal offset was said to increase the range of motion and decrease the incidence of impingement of the femoral head on the pelvis thus decrease the post-operative complications. Though CT scan is more accurate, the plain radiography is definitely the most cost effective and convenient method for offset measurement in the developing countries like India [14]. Our data showed that the average horizontal offset was 3.85 cm and 3.57 cm in male and female respectively.…”
Section: Methodsmentioning
confidence: 67%
“…This population has an increased life expectancy and an increased functional demand requiring, after THA, full ROM, quick and complete return to physical activity, longterm bone-implant fixation, and limited polyethylene wear and osteolysis [34,41]. In previous anatomic studies, it was shown the upper femoral anatomy may be distorted, particularly in young patients with frequent secondary forms of osteoarthritis [4,29,50]; consequently optimal fit-andfill of the metaphysis and extramedullary adaptation may be difficult to achieve in every case. A mean survival rate of 100% at 10 years was reported for a series of patients younger than 65 years without thigh pain, migration, or reoperation [56].…”
Section: Discussionmentioning
confidence: 99%
“…5,6,8 Unlike other studies, we measured the neckshaft angle based on the axis of the proximal femur. This will replicate the actual neck-shaft angle when performing total hip arthroplasty as the stem of the femoral component was designed to restore the anatomy of only the proximal femoral region.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The measurement of horizontal offset and the neck-shaft angle by radiographs, however, is affected by femoral neck version, hip rotation, and femoral bowing. [7][8][9] Although cadaveric studies investigating proximal femoral geometry by computed tomography have been more accurate, they have generally been based on specimens of asymmetrically mixed ages and genders.…”
mentioning
confidence: 99%